2007
DOI: 10.1111/j.1365-2699.2007.01749.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dating of the ‘Gondwanan’ plant family Proteaceae is only partially congruent with the timing of the break‐up of Gondwana

Abstract: Aim  The flowering plant family Proteaceae is putatively of Gondwanan age, with modern and fossil lineages found on all southern continents. Here we test whether the present distribution of Proteaceae can be explained by vicariance caused by the break‐up of Gondwana. Location  Africa, especially southern Africa, Australia, New Zealand, South America, New Caledonia, New Guinea, Southeast Asia, Sulawesi, Tasmania. Methods  We obtained chloroplast DNA sequence data from the rbcL gene, the rbcL‐atpB spacer, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
139
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(152 citation statements)
references
References 80 publications
5
139
1
2
Order By: Relevance
“…Using molecular dating, it was reported that Leucadendron evolved 40 millions year ago. (Barker et al 2007). Actinidia is dated even younger, approximately 20-26 million year ago (Qian and Yu 1991).…”
Section: Resultsmentioning
confidence: 99%
“…Using molecular dating, it was reported that Leucadendron evolved 40 millions year ago. (Barker et al 2007). Actinidia is dated even younger, approximately 20-26 million year ago (Qian and Yu 1991).…”
Section: Resultsmentioning
confidence: 99%
“…The same applies for Placostylus land snails, the sister group of which involves both the recently emerged Lord Howe Island and New Zealand ( Trewick et al in press). The New Caledonian sandalwood, Santalum austrocaledonicum, also differentiated recently, in this case from Vanuatu species 1-1.5 Ma (Harbaugh & Baldwin 2007 (Barker et al 2007). The New Caledonian freshwater shrimp genus Paratya (Page et al 2005) and galaxiid fishes (Waters et al 2000), sisters respectively to an Australian and a New Zealand group, are dated as younger than 12 and 9 Ma, respectively.…”
Section: Ancient Radiations or Repeated Dispersal?mentioning
confidence: 99%
“…Another example is the radiation of the cricket genus Agnotecous ( Eneopterinae), which includes many species with peculiar stridulatory apparatuses that emit songs in unusually high frequencies and with harmonic shifts (Robillard & Desutter-Grandcolas 2004;Robillard et al 2007). The cockroach subfamily Tryonicinae (Blattidae) includes the speciose genus Lauraesilpha, the members of which exhibit a unique combination of Araucaria (Setoguchi et al1998) Angustonicus (Murienne et al 2005) geckos (Bauer et al 2006) Sapotaceae (Bartish et al 2005) Proteaceae (Barker et al 2007) Paratya (Page et al 2005) diving beetles (Balke et al 2007a, b) galaxiid (Waters et al 2000) Tasmantis Scincidae (Smith et al 2007) sandalwoods ( behavioural traits, wood eating, intestinal ciliates and solitary habits (Grandcolas 1997;Murienne 2006; in press a, submitted). These characteristics recall those of panesthiine cockroaches (Blaberidae), which include many wood-eating species in Australasia and throughout the southwest Pacific (including Vanuatu and Lord Howe Islands), but with the exception of New Caledonia (Roth 1991).…”
Section: Local Radiation and Vacant Nichesmentioning
confidence: 99%
“…Distribution patterns are corroborated as 'Gondwanan' if they are considered old enough (e.g. Gamble et al, 2008), and rejected as 'Gondwanan' if they are not (Barker et al, 2007).…”
Section: Why We Need An Icanmentioning
confidence: 86%
“…Gondwana is an ancient supercontinent that existed from approximately 250-170 Ma, comprising what we now know as Australia, New Guinea, New Zealand, sub-Saharan Africa, Madagascar, India, Arabia, South America and Antarctica. The name 'Gondwana' has been used for all or just part of the once vast land-mass that began to break up in the mid-Jurassic: the 'Gondwana' of Philippe et al (2003) includes India, whereas the 'Gondwana' of Barker et al (2007) does not. Distribution patterns are corroborated as 'Gondwanan' if they are considered old enough (e.g.…”
Section: Why We Need An Icanmentioning
confidence: 99%